SIKAP TOLERANSI BERAGAMA ANTAR ANGGOTA HIMSOS FKIP UNTAN - Fahrul Rozi; Rustiyarso Rustiyarso; Izhar Salim (Universitas Tanjungpura, 2020)
AbstractThis study aims to examine how religious tolerance among members of the Himsos FKIP Untan. What is examined in this study is how the attitude of religious tolerance among members of Himsos FKIP Untan in the form of (1) tolerance attitude respecting other religions and (2) tolerance attitude in providing opportunities for religious practices of other religions. This research uses a qualitative approach with descriptive methods. Data collection techniques in this research are observation, interview and documentation study. Data collection tools used are observation guides, interview guides and documentation tools. The steps of data analysis include data reduction, data presentation and verification. Data validity by testing the credibility includes triangulation of techniques by checking the data at the same source with different techniques. The results of the study prove that tolerance in respecting beliefs among members of Himsos is well established and tolerance in giving opportunities for other religious worship practices is also goodKeywords : Attitude, Himsos, Religious Tolerance